A computed tomographic data-based vibrant bonebridge visualization tool. (May 2014) - Todt, I; Lamecker, H; Ramm, H; Ernst, A
<x content-type="archive" xml:space="preserve">Abstract</x> Aim Information about the temporal bone size and variations of anatomical structures are crucial for a safe positioning of the Vibrant Bonebridge B-FMT. A radiological based preoperative planning of the surgical procedure decreases the surgical time and minimizes the risk of complications. Materials and methods We developed a software tool, which allows a catch up of foreign DICOM data based CT temporal bone scans. The individual CT scan is transmitted into a 3D reconstructed pattern of the temporal bone. In this 3D reconstruction the individually favored position of the B- FMT should be found. Results The software allows a determination of a safe B-FMT position by identifying the individual relation of middle fossa, jugular bulb and external auditory canal. Skull thickness and screw length are contained parameters for the surgical planning. Conclusion An easy to handle software tool allows a radiologically data based safe and fast surgical positioning of the B-FMT.